2016
DOI: 10.1037/sgd0000172
|View full text |Cite
|
Sign up to set email alerts
|

The impact of discrimination on mental health symptomatology in sexual minority immigrant Latinas.

Abstract: At a time when serious xenophobic and heterosexist sentiment is at the forefront of our country's political climate, it is incredibly important to explore and understand the links between discrimination and mental health for vulnerable communities. The purpose of this study was to carry out a preliminary exploration of the relations between acculturation to the United States (U.S.), discrimination related to ethnic minority and sexual minority statuses, and mental health symptomatology (depression, posttraumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 39 publications
2
49
0
1
Order By: Relevance
“…Consistently, previous studies on the general LGBTQ* population as well as refugees after resettlement also showed heightened symptom levels of depression and anxiety (Cochran et al 2003;King et al 2008;Valentine & Shipherd 2018). While there are several studies reporting various mental health burdens in LGBTQ* refugees and immigrants (Alessi 2016;Cerezo 2016;Gowin et al 2017;Hopkinson et al 2017;Ogunbajo et al 2018;Rhodes et al 2013;Yamanis et al 2018), our study highlights the theme of subjective worsening of both discrimination experiences as well as mental distress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistently, previous studies on the general LGBTQ* population as well as refugees after resettlement also showed heightened symptom levels of depression and anxiety (Cochran et al 2003;King et al 2008;Valentine & Shipherd 2018). While there are several studies reporting various mental health burdens in LGBTQ* refugees and immigrants (Alessi 2016;Cerezo 2016;Gowin et al 2017;Hopkinson et al 2017;Ogunbajo et al 2018;Rhodes et al 2013;Yamanis et al 2018), our study highlights the theme of subjective worsening of both discrimination experiences as well as mental distress.…”
Section: Discussionsupporting
confidence: 90%
“…Sexual minority immigrants from Central/South America or Africa living in the USA also reported high levels of mental distress such as symptoms of depression, post-traumatic stress, and substance abuse. These symptoms were associated with discrimination experiences in their countries of origin as well as in their host country, socioeconomic factors, and internalized stigma (Cerezo 2016;Ogunbajo et al 2018;Rhodes et al 2013).…”
Section: Mental Health Of Lgbtq* Refugeesmentioning
confidence: 99%
“…Acculturation and discrimination (based on race/ethnicity, sexual identity, gender, or gender identity) were each independently and significantly associated with substance use; the association between acculturation and substance use was partially mediated by discrimination. In unadjusted analyses of data from a national convenience sample of Latina immigrant SMW, Cerezo [79] found that discrimination based on ethnic minority status and on sexual minority status were significantly associated with substance use. However, these associations were attenuated and no longer significant when adjusting for age, income, education, and acculturation.…”
Section: Racial/ethnic Differences In Aod Usementioning
confidence: 99%
“…Second, internalized heterosexism could stem from the internalization of day-to-day experiences of discrimination as well as increased likelihood of exposure to criterion A traumas due to one’s lesbian or bisexual sexual orientation (Hatzenbuehler, 2009). These proximal stressors have been associated with greater psychological distress and increased substance use among SMW (Cerezo, 2016; Lehavot & Simoni, 2011; Szymanski & Kashubeck-West, 2008), although research on their impact on PTSD symptoms is limited. In sum, from this perspective, exposure to both minority-specific and non-minority-specific distal stressors, as well as internalization of these experiences in the form of both minority-specific and non-minority-specific proximal stressors, play a role in consequently leading to the development and maintenance of PTSD.…”
mentioning
confidence: 99%